Effect of coagulation factors FXIa, FXIIa, F alpha-XIIa, F beta-XIIa and FXIIIa on platelet function. (3rd October 2022) - Wildeis, L; Ziese, J; Helten, C; Benkhoff, M; Mourikis, P; Zako, S; Petzold, T; Levkau, B; Zeus, T; Kelm, M; Polzin, A
Abstract: Background: FXa has recently been shown to active platelets via protease activated receptor. Direct inhibition of FXa leads to reduced platelet reactivity and arterial thrombosis. It is not known, if other coagulation factors besides FXa and FIIa directly activate platelets. In this study, we hypothesized that FXIa, FXIIa, Fα-XIIa, Fβ-XIIa and FXIIIa directly active platelets. Purpose: Direct inhibitors of above mentioned factors are currently in clinical trials. Hence, investigation of coagulation factors' non-canonical effects beyond activation of the coagulation cascade are of great importance. Methods: Platelet reactivity was measured using light transmission aggregometry (LTA) and flow cytometry. Ex-vivo stimulation of washed platelets was conducted using adenosine diphosphate (ADP) and thrombin receptor activator peptide (TRAP). Results: FXIa, FXIIa, Fα-XIIa, Fβ-XIIa and FXIIIa have no direct effect on platelet function in terms of aggregation (Maximum of aggregation: FXIa: 2.799±1, 823%, FXIIa: 1, 174±1, 080%, Fα-XIIa: 1, 663±1, 680%, Fβ-XIIa: 1, 060±1, 356%, Fα-XIIa + Fβ-XIIa 1, 790±2, 327% and FXIIIa: 1, 345±1, 060%). Also, incubation of platelets does not cause expression of P-selectin (FXIa: 4, 346±4, 650%, FXIIa: 7, 072±6, 098%, Fα-XIIa: 9, 124±6, 075%, Fβ-XIIa: 4, 556±4, 693%, Fα-XIIa + Fβ-XIIa 8, 070±4, 342% and FXIIIa: 5, 166±5, 512%). Conclusion: FXIa, FXIIa, Fα-XIIa, Fβ-XIIa and FXIIIa have no direct effect on platelet function in terms of aggregation and P-selectin expression. Thus, existing pharmacological inhibitors of these factors are to be classified as purely anticoagulant and do not exert non-canonical effects on platelet activation. Funding Acknowledgement: Type of funding sources: None.